2014
DOI: 10.1016/j.ejbt.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a pheasant (Phasianus colchicus) spermatogonial stem cell line for the production of interspecies germ line chimeras

Abstract: a b s t r a c tBackground: Spermatogonial stem cells (SSCs) are important for the production of interspecies germ line chimeras. The interspecies germ cell transfer technique has been suggested as a way to conserve endangered birds. Our objective was to develop a technique for restoring endangered birds by developing interspecies germ line chimeras between pheasant (Phasianus colchicus) and chicken (Gallus gallus) with SSCs. Results: SSCs were isolated from the surgically removed testis of a pheasant. Growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…GFR α -1 mRNA and protein expression is detected mainly in type A SPG close to the basement membrane of the seminiferous tubule, and GFR α -1-expressing SPG produce the progenies in recipient chickens [ 95 , 96 ]. Spermatogonia, isolated from juvenile and adult quail using a differential plating technique, express GFR α -1, and SPG cultured from adult pheasant testes also express GFR α -1 [ 97 , 98 ]. Mammalian GFR α -1 is expressed in gonocytes and undifferentiated type A SPG of the testis and cultured (or isolated) SSCs (Supplementary Table 1 ).…”
Section: Class-crossed Molecular Markers Of Spermatogonial Stem Cells...mentioning
confidence: 99%
“…GFR α -1 mRNA and protein expression is detected mainly in type A SPG close to the basement membrane of the seminiferous tubule, and GFR α -1-expressing SPG produce the progenies in recipient chickens [ 95 , 96 ]. Spermatogonia, isolated from juvenile and adult quail using a differential plating technique, express GFR α -1, and SPG cultured from adult pheasant testes also express GFR α -1 [ 97 , 98 ]. Mammalian GFR α -1 is expressed in gonocytes and undifferentiated type A SPG of the testis and cultured (or isolated) SSCs (Supplementary Table 1 ).…”
Section: Class-crossed Molecular Markers Of Spermatogonial Stem Cells...mentioning
confidence: 99%
“…SSCs, the other type of male germline-competent stem cells in adult testes that are precursors in spermatogenesis, have been successfully isolated from mammalian species, cultured, and used for transgenic production 14 , 15 . SSCs of several bird species including chickens, pheasants, and quails have been isolated and cultured, but practical applications for producing transgenic birds using these cells are limited 16 20 . In zebra finch, although studies have reported the isolation and manipulation of PGCs, reports of exogenous genes being efficiently delivered into these cells are limited 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%